The music practitioner: Research for the music performer, teacher and listener - Davidson, Jane W. (Burlington Ashgate, 2004)
This is the first book to provide a wide assessment of what ptactical benefits this research can bring to the music practitioner. With 25 chapters be writers representing a broad range of perspectives, this volume is able to highlight many of the potential links between music reserach and practice.